Impacts of mining on property values in Kalgoorlie-Boulder, Western Australia. (October 2020) - Kolala, Chomba; Polyakov, Maksym; Fogarty, James
Abstract: Mining activities have a positive impact on local communities through providing formal employment opportunities in the local area. However, the air and noise pollution associated with surface mining represent a negative externality for residents in communities near mining activity. To support urban planning processes, accurate information on both the positive and negative impacts of surface mining is required. In this study, we estimate the dis-amenity of proximity to a large open-pit gold mine in Kalgoorlie, Western Australia, that has been capitalised into residential property values. To estimate the impact of proximity to the mine on property values, we use sales data for 21, 850 residential properties sold in Kalgoorlie-Boulder between 1990 and 2018. We use distance to the mine as a measure of the impact. We control for spatial heterogeneity using spatial fixed effects. We found that residential properties located within two kilometres of the mine trade at a 20% to 30% discount to similar residential properties located at least six to seven kilometres from the mine. Our results can be used for planning appropriate buffer zones around mining activities. Highlights: Mining provides economic benefits but also creates dis-amenities for adjacent communities. Hedonic pricing method was used to examine the dis-amenity of an open-cut mine. Local residents pay 20%–30% less for properties located within 2 Km of the mine, relative to the properties located 6 to 7 Km away. The study can be used by planners to set appropriate buffer zones around mines.